Antibiofilm Activities of Fluoride Releasing Restorative Materials - Tartici Mehmet; Tartici Tuğçe; Karaca Başar; Gür Gürkan (Balkan Stomatological Society, 2020)
Backround/Aim: The purpose of this in vitro study is to evaluate the antibiofilm and antimicrobial activities of 5 different restorative materials that release fluoride.